26‐3: Scalability and Homogeneity of Slot‐Die Coated Metal Oxide Semiconductor for TFTs. Issue 1 (May 2016) - Takata, Ryo; Neumann, Anita; Weber, Dennis; Pham, Duy-Vu; Anselmann, Ralf; Kitamura, Yoshitaka; Kakimura, Takashi; Suzuki, Satoshi; Minami, Shigeki; Kodama, Mitsumasa
Abstract : An indium oxide based precursor solution has been developed by spin‐coating method. In order to apply this material to a mass production, material, process and equipment optimizations for slot die coating have been implemented. Slot die coating is a cost‐effective, scalable process and already applied to photoresist materials in the display industry. The indium oxide based precursor solution has been coated on bare glasses and TFT substrates by a mass production type slot die coater. Mobility of over 10cm 2 /Vs is achieved for the first time for large area at annealing temperatures of 350°C. The homogeneity of the film will be presented.